Exploring the dual role of Mangifera indica L. in regulating immune response and pain persistence in inflammatory bowel disease - Elena Lucarini; Anna Schettino; Noemi Marigliano; Clara Ciampi; Martina Smimmo; Francesca Romano; Antonio Paolillo; Luana Izzo; Jenefa Begum; Adel Abo Mansour; Nunzia Iaccarino; Antonio Randazzo; et al. (Pharmacological Research)
Inflammatory bowel disease (IBD), encompassing ulcerative colitis and Crohn’s disease, is characterized by chronic intestinal inflammation and immune dysregulation, driven mainly by Th1 and Th17 cells and sustained by pro-inflammatory cyto-chemokines. This inflammatory milieu is associated with visceral pain, a key symptom affecting patient quality of life. Addressing both gut inflammation/immunity and visceral pain is crucial for improving IBD therapy. This study assessed the therapeutic potential of Mangifera indica L. extract (MIE), a mangiferin-rich formulation, in a DNBS-induced colitis model in rats. MIE treatment administered either simultaneously or post-DNBS induction, significantly reduced pathogenic Th1 and Th17 cell infiltration, along with pro-inflammatory cytokines (IL-1β, TNF-α) and chemokines (CXCL1, CXCL2), though histopathology showed no significant improvements in tissue healing. Additionally, MIE restored microbiota–derived short-chain fatty acids (acetate and butyrate) in colon and faecal samples. Importantly, MIE alleviated post-inflammatory visceral hypersensitivity, reducing the abdominal withdrawal reflex (AWR) to colorectal distension (CRD), after either acute or repeated treatment. These findings suggest that MIE, in the context of nutraceuticals and functional foods, shows promise as a dual-action therapeutic strategy for complementary and/or adjuvant therapy in IBD.